I survived : the Galveston hurricane, 1900 - Tarshis, Lauren (Tarshis, Lauren. I survived., 2021)
"It's 1900, and Charlie feels lucky to live in Galveston, Texas. Sure, there are storms sometimes. But nobody worries about hurricanes. Even a famous weather expert says it's impossible for a strong hurricane to strike Galveston. Which is why few people worry on the morning of September 8, when a big storm starts to brew. but Charlie watches with growing horror as monster waves rise up from the sea, as the wind starts to scream. by night, much of the city is under twenty feet of water. Will Charlie find a way to survive the storm of the century?"--Back cover.